Optimization of 4D vessel‐selective arterial spin labeling angiography using balanced steady‐state free precession and vessel‐encoding. (13th April 2016) - Okell, Thomas W.; Schmitt, Peter; Bi, Xiaoming; Chappell, Michael A.; Tijssen, Rob H. N.; Sheerin, Fintan; Miller, Karla L.; Jezzard, Peter
Abstract : Vessel‐selective dynamic angiograms provide a wealth of useful information about the anatomical and functional status of arteries, including information about collateral flow and blood supply to lesions. Conventional x‐ray techniques are invasive and carry some risks to the patient, so non‐invasive alternatives are desirable. Previously, non‐contrast dynamic MRI angiograms based on arterial spin labeling (ASL) have been demonstrated using both spoiled gradient echo (SPGR) and balanced steady‐state free precession (bSSFP) readout modules, but no direct comparison has been made, and bSSFP optimization over a long readout period has not been fully explored. In this study bSSFP and SPGR are theoretically and experimentally compared for dynamic ASL angiography. Unlike SPGR, bSSFP was found to have a very low ASL signal attenuation rate, even when a relatively large flip angle and short repetition time were used, leading to a threefold improvement in the measured signal‐to‐noise ratio (SNR) efficiency compared with SPGR. For vessel‐selective applications, SNR efficiency can be further improved over single‐artery labeling methods by using a vessel‐encoded pseudo‐continuous ASL (VEPCASL) approach. The combination of a VEPCASL preparation with a time‐resolved bSSFP readout allowed the generation of four‐dimensional (4D; time‐resolved three‐dimensional, 3D) vessel‐selective cerebral angiograms in healthy volunteers with 59 ms temporal resolution. Good quality 4D angiograms were obtained in all subjects, providing comparable structural information to 3D time‐of‐flight images, as well as dynamic information and vessel selectivity, which was shown to be high. A rapid 1.5 min dynamic two‐dimensional version of the sequence yielded similar image features and would be suitable for a busy clinical protocol. Preliminary experiments with bSSFP that included the extracranial vessels showed signal loss in regions of poor magnetic field homogeneity. However, for intracranial vessel‐selective angiography, the proposed bSSFP VEPCASL sequence is highly SNR efficient and could provide useful information in a range of cerebrovascular diseases. © 2016 The Authors. NMR in Biomedicine published by John Wiley & Sons Ltd. Abstract : A time‐resolved balanced steady‐state free precession readout was optimized for arterial spin labeling dynamic angiography, compared with spoiled gradient echo, and combined with a vessel‐encoded preparation to allow the generation of 4D (dynamic 3D) non‐contrast vessel‐selective angiograms with high spatial and temporal resolution. Signal‐to‐noise ratio efficiency and vessel‐selectivity were shown to be high. A dynamic 2D protocol took only 1.5 min. Potential applications include the assessment of collateral blood flow and evaluation of the arterial supply to lesions.